Perceived readiness of young adults with type 1 diabetes and their parents/guardians to transition from pediatric care to adult care - Yaeger, Kara M. (My University, 2011)
The purpose of the study is to assess perceived readiness of young adults with type 1 diabetes mellitus who will transition from pediatric diabetes care to adult diabetes care. An additional objective is to gather information to plan for a transition program.
Keywords: Medical care -- United States -- Wisconsin; Health promotion -- United States -- Wisconsin; Diabetes Mellitus -- therapy -- United States -- Wisconsin; Diabetes -- Study and teaching -- United States -- Wisconsin; Diabetes Mellitus, Type 1 -- epidemiology -- United States -- Wisconsin; Diabetes.; Diabetics.